Low-Input High-Molecular-Weight DNA Extraction for Long-Read Sequencing From Plants of Diverse Families - Russo, Alessia; Mayjonade, Baptiste; Frei, Daniel; Potente, Giacomo; Kellenberger, Roman T.; Frachon, Léa; Copetti, Dario; Studer, Bruno; Frey, Jürg E.; Grossniklaus, Ueli; Schlüter, Philipp M. (Frontiers in Plant Science, 2022)
Long-read DNA sequencing technologies require high molecular weight (HMW) DNA of adequate purity and integrity, which can be difficult to isolate from plant material. Plant leaves usually contain high levels of carbohydrates and secondary metabolites that can impact DNA purity, affecting downstream applications. Several protocols and kits are available for HMW DNA extraction, but they usually require a high amount of input material and often lead to substantial DNA fragmentation, making sequencing suboptimal in terms of read length and data yield. We here describe a protocol for plant HMW DNA extraction from low input material (0.1 g) which is easy to follow and quick (2.5 h). This method successfully enabled us to extract HMW from four species from different families (Orchidaceae, Poaceae, Brassicaceae, Asteraceae). In the case of recalcitrant species, we show that an additional purification step is sufficient to deliver a clean DNA sample. We demonstrate the suitability of our protocol for long-read sequencing on the Oxford Nanopore Technologies PromethION® platform, with and without the use of a short fragment depletion kit.